“Ulysses 1922-2022: reinvenciones creativas” - Anne Fogarty (Estudios Irlandeses, 2023)
Joycean anniversaries have always served as important milestones. Inevitably, they further add to Joyce’s worldwide brand and cement his value as an incontestably global author. But more importantly they also provide opportunities to revisit and re-evaluate his work for aficionados and open it up for the uninitiated. In Ireland, significant years such as 1982, the anniversary of Joyce’s birth, and 2004, the anniversary of Bloomsday, have proven vital for an increased appreciation of Joyce as a writer who directly connects with and speaks to contemporary Ireland. Joyce has in recent decades transmogrified from a scandalous author, upstart outsider, and foreign import to a kindred spirit and congenial but always challenging artistic role model.